Combinatorial Strategies to Target Molecular and Signaling Pathways to Disarm Cancer Stem Cells - Catara, Giuliana; Colanzi, Antonino; Spano, Daniela (Frontiers in Oncology, 2021)
Cancer is an urgent public health issue with a very huge number of cases all over the world expected to increase by 2040. Despite improved diagnosis and therapeutic protocols, it remains the main leading cause of death in the world. Cancer stem cells (CSCs) constitute a tumor subpopulation defined by ability to self-renewal and to generate the heterogeneous and differentiated cell lineages that form the tumor bulk. These cells represent a major concern in cancer treatment due to resistance to conventional protocols of radiotherapy, chemotherapy and molecular targeted therapy. In fact, although partial or complete tumor regression can be achieved in patients, these responses are often followed by cancer relapse due to the expansion of CSCs population. The aberrant activation of developmental and oncogenic signaling pathways plays a relevant role in promoting CSCs therapy resistance. Although several targeted approaches relying on monotherapy have been developed to affect these pathways, they have shown limited efficacy. Therefore, an urgent need to design alternative combinatorial strategies to replace conventional regimens exists. This review summarizes the preclinical studies which provide a proof of concept of therapeutic efficacy of combinatorial approaches targeting the CSCs.